p(x) =x² - 14x+ 53 by q(x) =x-6
Answers
Answered by
5
please mark as brainlist answer and follow me please thank answer ☺️ ☺️☺️☺️
give me 20 thanks I will give you 30 thanks.promise
Attachments:
![](https://hi-static.z-dn.net/files/dd5/531d8102b9dc95178fc469890e3c02af.jpg)
Answered by
1
Answer:
x-6=0
x=6
p(6)=6^2-14×6+53
=36-84+53
=53+36-84
=89-84
p(6)=5
Step-by-step explanation:
please mark as brainliest
Similar questions
Math,
5 months ago
English,
5 months ago
Environmental Sciences,
5 months ago
Physics,
10 months ago
Math,
10 months ago